KONTRIBUSI SILAT TUO DALAM TARI RANTAK KARYA GUSMIATI SUID - Efrida Efrida (Institut Seni Indonesia Surakarta, 2013)
Rantak is a dance choreography created by Gusmiati Suid on 1987. The dance is still beenlearned at schools, colleges, and dance studios in West Sumatra. Beyond West Sumatra, thedance also often becomes a learning material in creating Minangkabau style dance. Rantak Dancehas become a well–known Minangkabau cultural icon in Indonesia and abroad. The Rantak Danceadapted Minangkabau’s silat tuo moves as the choreography idea. Not only the moves, the danceadapted the essence and the philosophy of silat tuo, these facts distinguish Rantak Dance fromother Minangkabau dances. The creation process that was taken by Gusmiati Suid was veryamazing. She was doing silat tuo in–depth learning process for six years at several nagari iniMinangkabau. Her seriousness showed that Rantak Dance was a legitimate monumental danceby a choreographer named Gusmiati Suid.